Sosialisasi Dasar Keselamatan dan Kesehatan Kerja Pengelasan untuk Pegawai PMT PTPN IV Dolok Ilir - Sitepu, Evi Christiani; Purba, Switamy Angnitha; Sitinjak, Anna Angela; Lumbantoruan, Sorta; Kurnia, Dian; Saragih, Koko Pratama; Tarigan, Nurlianna; Manik, Toba Sastrawan; Maulidna, Maulidna; Nelza, Novia; Samiriadi, Samiriadi; Tambunan, Diman Raymond S (Program Studi Pendidikan Guru Sekolah Dasar Universitas Flores Ende, 2023)
The application of Occupational Safety and health (K3) is very important in the work environment because it is closely related to the risk of accidents, safety and health when carrying out work. Various efforts have been made by the Tenera machinery factory (PMT) PTPN IV to minimize work accidents and diseases caused by work by installing warning signs, the use of complete personal protective equipment (PPE), providing good nutrition and regular health checks. However, the lack of awareness of K3 is still found in PMT PTPN IV Dolok Ilir workers. This can be seen from the still finding of minor work accidents and occupational health effects shown from the results of employee health reports. The methods used in this service activity are socialization, training, discussion on the basics of K3 welding for employees of PMT PTPN IV, so that factory employees are able to identify potential hazards that can occur in the workplace and accident prevention measures. The results of the socialization and training of welding K3 activities that have been carried out are expected to increase employee awareness of the importance of K3. So that the company is able to maintain the zero accident predicate.